2012
DOI: 10.1186/1758-2555-4-28
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular corrective osteotomy for malunited Hoffa fracture: A case report

Abstract: Hoffa fracture, an isolated coronal plane fracture of the posterior aspect of the femoral condyle, is known as an unstable, intra-articular fracture, and therefore, operative treatment is recommended. However, insufficient open reduction or failure of fixation may lead to malunion. We performed intra-articular corrective osteotomy for a malunited Hoffa fracture in a 31-year-old man and obtained good functional and radiographic results. This report suggests that intra-articular corrective osteotomy for malunite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Corrective osteotomy after a malunited intra-articular fracture is reported in other parts such as the distal radius and tibial plateau, which led to satisfactory results [6,7]. There are two case reports of corrective osteotomy for the malunited Hoffa fracture [3,4]. They have concluded that the malunited fracture can lead to the restriction of the range of movement, as well as pain and subsequent osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrective osteotomy after a malunited intra-articular fracture is reported in other parts such as the distal radius and tibial plateau, which led to satisfactory results [6,7]. There are two case reports of corrective osteotomy for the malunited Hoffa fracture [3,4]. They have concluded that the malunited fracture can lead to the restriction of the range of movement, as well as pain and subsequent osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The range of motion has improved to 0°of knee extension and 120°of knee flexion, and the femorotibial angle is 172°. There is a mild bony spur formation over the tibia side of the knee, but there is (4). Lateral plate and medial plate were used to bridge the metaphyseal lesion and articular lesion (5,6).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…3 Review of literature on Hoffa's fracture shows a case report of intraarticular corrective osteotomy done as a salvage treatment for malunited lateral Hoffa's fracture. 4 Intraarticular corrective osteotomy for a malunited medial Hoffa fracture is technically even more challenging. Reconstructive osteotomy for a symptomatic malunited medial Hoffa fracture has not been reported in the English literature to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, non-operative treatment results in poor outcomes, including displacement, malunion, non-union and avascular necrosis 8 14–17. Open reduction and anatomical fixation, followed by early rehabilitation, may reduce the risk of these complications and result in better functional outcomes 8 18.…”
Section: Introductionmentioning
confidence: 99%